PENERAPAN MODEL COSO UNTUK PENINGKATAN FUNGSI PENGENDALIAN INTERNAL: STUDI PADA AGENCY ADMINISTRAÇÃO DE AEROPORTO E NAVEGAÇÃO AÉREA DE TIMOR-LESTE - Verissimo Nai Sia (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Implementation of internal controls is a basic principle for internal/external auditing. Internal control becomes a basic framework to operate effectiveness and efficiency of organization activities. Implementation of the COSO internal control for ANATL agency is to improve the actual system of internal control at Dili airport, and also as requirements from ICAO standards. Requirements of air transport services, such as: (1) increased efficiency, (2) reduce costs, and (3) safety and security. This study tried to find out the implementation and problems of internal control in the agency ANATL, by comparison with the COSO framework.Theories of COSO internal control model stated three groups of the objectives, namely: 1) Effectiveness and efficiency of operations, 2) Reliability of financial reporting, and 3) Compliance with applicable laws and regulations. Achieving the three objectives there are five basic components of internal control system such as: Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring.The study was conducted with qualitative methods to verify the theory of proposition 1: If implementation of internal control as a whole, then the performance of agency ANATL will be very good, and proposition 2: Quality of internal control is getting better, the arising of risk could be reduced and fraud preventable.The results had shown that implementation of internal control as framework COSO order in the agency ANATL was very weak. Weakness almost among categories and components of internal control therefore not applied completely. The category of weakness was financing reporting and compliance with laws and regulations. While the components were very weak such as control environment, control activities and monitoring. The proposition 1 is answered: the implementation internal control in agency ANATL is not completed cause poor performance. Poor quality of internal controls or inadequate, then the proposition 2 answered: the poor quality of the internal control will be risk and fraud.